Perspectives for the reconstruction of 3D chromatin conformation using single cell Hi-C data - Pavel I. Kos (Public Library of Science (PLoS), 2021)
Construction of chromosomes 3D models based on single cell Hi-C data constitute an important challenge. We present a reconstruction approach, DPDchrom, that incorporates basic knowledge whether the reconstructed conformation should be coil-like or globular and spring relaxation at contact sites. In contrast to previously published protocols, DPDchrom can naturally form globular conformation due to the presence of explicit solvent. Benchmarking of this and several other methods on artificial polymer models reveals similar reconstruction accuracy at high contact density and DPDchrom advantage at low contact density. To compare 3D structures insensitively to spatial orientation and scale, we propose the Modified Jaccard Index. We analyzed two sources of the contact dropout: contact radius change and random contact sampling. We found that the reconstruction accuracy exponentially depends on the number of contacts per genomic bin allowing to estimate the reconstruction accuracy in advance. We applied DPDchrom to model chromosome configurations based on single-cell Hi-C data of mouse oocytes and found that these configurations differ significantly from a random one, that is consistent with other studies. Author summary Reconstruction of 3D configuration of chromosomes based on single cell Hi-C data (contact matrix) constitutes an important way to understand the specific features of genome packaging in individual cells. For this purpose, we develop method DPDchrom based on dissipative particle dynamics. Two sources of the contact dropout, contact radius change and random contact sampling, have different impact to the reconstruction accuracy suggesting unequal value of contacts. We found the exponential dependence of the reconstruction accuracy on the number of contacts per genomic bin. We reconstructed entire nucleus of mouse using single cell Hi-C data and found significant dissimilarity of conformations reconstructed using experimental and shuffled data. These findings open perspectives to study 3D arrangement of cis-regulatory elements orchestrating transcription program.